Employee Representation Legislations and Innovation - Filippo Belloc (Fondazione Eni Enrico Mattei (FEEM), 2016)
We analyse how countries' innovation outcomes are affected by national legislations of worker participation to corporate governance. We develop a model of employee representation laws (ERL) and innovation in the presence of incomplete labour contracts and predict heterogeneous ERL effects across different systems of dismissal regulation. We then perform a panel regression analysis, exploiting 2-digit panel data for 21 manufacturing sectors of USA, UK, India, France and Germany, over the 1977-2005 period. We find that ERL effects on aggregate innovation output are positive, statistically significant and higher in magnitude where national labour laws impose significant firing costs to the firm with respect to institutional settings in which firing costs are low or absent. These results are robust to possible technology selection dynamics, endogeneity and institutional changes in the legal system of patent protection. We also estimate ERL effects on innovation conditional on firing costs at an industry level and show that the impact of ERL is relatively larger in those sectors where the human capital contribution to production is higher. Our results have relevant implications for the optimal design of employee representation legislations.
Keywords: K31; O31; P51; 330; Employee Representation Law; Innovation; Panel data